THE EFFECT of TOMATO JUICE AND DRAGON FRUIT JUICE ON 2-HOUR POST PRANDIAL BLOOD GLUCOSE LEVELS IN TYPE 2 DIABETES MELITUS PATIENTS IN BAKULAN VILLAGE, KEMANGKON DISTRICT - Frizka Mawar Mayssiana; Dwi Astuti; Eko Julianto (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Background: Type 2 diabetes mellitus is a chronic metabolic disorder characterized by elevated blood glucose levels due to insulin resistance or impaired insulin secretion. One effort to help lower blood glucose levels is through complementary therapy using natural ingredients such as tomato juice and dragon fruit juice, which contain various active compounds such as lycopene, fiber, vitamin C, and antioxidants.Objective: To determine the effect of tomato juice and dragon fruit juice on 2-hour post prandial blood glucose levels in type 2 diabetes mellitus patients. Methods: This research is a case study with two subjects who met the inclusion criteria. The intervention was administered for 7 days, during which subjects consumed tomato juice and dragon fruit juice. Blood glucose levels were measured before and after the intervention using an Easy Touch device. Results: The study showed a decrease in blood glucose levels after administration of both juices. This indicates that the combination of tomato juice and dragon fruit juice can significantly lower blood glucose levels. Conclusion: Administering tomato juice and dragon fruit juice can be an effective complementary therapy in lowering blood glucose levels in patients with type 2 diabetes mellitus.